Diabrotica collicola (Coleoptera: Chrysomelidae), a new species of leaf beetle from Argentina and key to species of the Diabrotica virgifera group and relatives - Cabrera, Nora; Walsh, Guillermo Cabrera (Zootaxa, 2010)
The new species Diabrotica collicola Cabrera & Cabrera Walsh is described and illustrated based on specimens collected from Balcozna, Catamarca Province (Argentina). A full description is provided and includes adding morphological characters of the mouthparts, hind wing venation, binding patch, metendosternite, and details of male and female genitalia previously overlooked for the genus. Diabrotica collicola is recognized by the following characters: general color parrot green with yellowish vittae, genal space less than 1/4 maximum length of the eye, antennomeres 2 and 3 subequal in males, 3 longer in females, both antennomeres together more than length 1/2 of 4 in both sexes, prothoracic and mesothoracic tarsi of males with ventral adhesive patch, internal sac of the median lobe with four sclerites. Differences with similar species D. mutabilis Baly, D. fulvofasciata Jacoby, D. mapiriensis gussi Krysan & Smith and D. porracea Harold are discussed. A key to D. collicola and similar species is provided.